Impact of preexisting diabetes mellitus on cardiovascular and all-cause mortality in patients with atrial fibrillation: A meta-analysis - Xu, Juan; Sun, Yimeng; Gong, Dandan; Fan, Yu (Frontiers in Endocrinology, 2022)
Objective: To determine the impact of preexisting diabetes mellitus on cardiovascular and all-cause mortality in patients with atrial fibrillation (AF) by conducting a meta-analysis. Methods: PubMed and Embase databases were comprehensively searched for relevant studies publishing until May 19, 2022. Cohort studies or post hoc analysis of clinical trials that investigated the association of diabetes mellitus with cardiovascular or all-cause mortality in AF patients were included. Results: A total of 21 studies with 526,136 AF patients were identified. The pooled prevalence of diabetes mellitus in patients with AF was 26%. The summary multivariable-adjusted risk ratio (RR) of all-cause mortality was 1.37 (95% confidence intervals [CI] 1.23–1.53) for patients with diabetes versus those without diabetes. Moreover, diabetes mellitus was also associated with an increased risk of cardiovascular mortality (RR 1.46; 95% CI 1.34–1.58). Stratified analyses suggested that the impact of diabetes on all-cause and cardiovascular mortality was consistently observed in each named subgroup. Conclusion: The presence of diabetes mellitus in patients with AF is associated with an increased risk of cardiovascular and all-cause mortality, even after adjustment for important confounding factors.